2022
DOI: 10.3390/plants11212912
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Soil Bacteria from Arid Zones to Increase Plant Tolerance to Drought: Growth and Biochemical Status of Maize Inoculated with Plant Growth-Promoting Bacteria Isolated from Sal Island, Cape Verde

Abstract: Climate change and anthropogenic activities are responsible for extensive crop yield losses, with negative impact on global agricultural production. The occurrence of extreme weather events such as drought is a big challenge for agriculture, negatively impacting crops. Thus, methodologies reducing crop dependence on water will be a great advantage. Plant roots are colonized by soil bacteria, that can establish beneficial associations with plants, increasing crop productivity and plant tolerance to abiotic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Zhou et al (2022) investigated sweet potato plants under water stress and found proline accumulation associated with positive regulation of SOD and CAT activities. These characteristics help plants cope with drought (Ebrahimi et al, 2016;Cruz et al, 2022). Like other abiotic stresses, drought results in the accumulation of ROS, primarily in chloroplasts and to some extent in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2022) investigated sweet potato plants under water stress and found proline accumulation associated with positive regulation of SOD and CAT activities. These characteristics help plants cope with drought (Ebrahimi et al, 2016;Cruz et al, 2022). Like other abiotic stresses, drought results in the accumulation of ROS, primarily in chloroplasts and to some extent in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the irrigation schedules were calculated for the different hydrological years during the maize growth period in Heilongjiang Province. In agricultural production, farmers should also be guided to irrigate at the right time and amount, taking into account the actual local conditions including climate, soil, crop growth, and irrigation efficiency [62]. Water-saving technologies and soil moisture conservation measures for crops, such as plastic film mulching and straw incorporation, should be reasonably carried out [63].…”
Section: Discussionmentioning
confidence: 99%
“…Cruz et al [16] isolated and characterized bacterial strains from Sal Island (Cape Verde) and evaluated their osmotic tolerance and a number of their growth-promotion traits. The osmo-tolerant strains were used to inoculate maize plants, and the drought-tolerance of inoculated plants was evaluated by measuring their germination, growth, and physiological and biochemical parameters.…”
Section: An Overview Of This Special Issue's Articlesmentioning
confidence: 99%